2021
DOI: 10.1007/s11356-021-17691-0
|View full text |Cite
|
Sign up to set email alerts
|

A workflow to investigate the impacts of weathered multi-walled carbon nanotubes to the mud snail Lymnaea stagnalis

Abstract: Although the development and application of nanomaterials is a growing industry, little data is available on the ecotoxicological effects on aquatic organisms. Therefore, we set up a workflow to address the potential uptake of weathered multi-walled carbon nanotubes (wMWCNTs) by a model organism, the pulmonary mud snail Lymnaea stagnalis (L. stagnalis), which plays an important role in the food web. It represents a suitable organism for this approach because as a grazer it potentially ingests large amounts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 94 publications
(125 reference statements)
1
19
0
Order By: Relevance
“…Finally, after 28 days of depuration, no wMWCNTs were detected in the gut or digestive glands. Thus, we show the fate of wMWCNTs entering the cells of L. stagnalis, but after a period of depuration, the snails are able to recover (see also Weise et al 2021). There might be greater risk if there is no depuration phase, and the wMWCNTs are ingested over a long period of time.…”
Section: Histology and Electron Microscopy Of L Stagnalis Digestive G...mentioning
confidence: 77%
See 2 more Smart Citations
“…Finally, after 28 days of depuration, no wMWCNTs were detected in the gut or digestive glands. Thus, we show the fate of wMWCNTs entering the cells of L. stagnalis, but after a period of depuration, the snails are able to recover (see also Weise et al 2021). There might be greater risk if there is no depuration phase, and the wMWCNTs are ingested over a long period of time.…”
Section: Histology and Electron Microscopy Of L Stagnalis Digestive G...mentioning
confidence: 77%
“…In the midgut lumen, large bundles of wMWCNTs can be found (Fig. 4a, b, see also Weise et al 2021), but no wMWCNTs could be detected in its epithelial cells. This is consistent with observations by Petersen et al (2009) who showed the presence of MWCNTs in the intestinal lumen of D. magna, The digestive epithelium with B-cells which contain many phagocytic granules of different sizes (e.g.…”
Section: Histology and Electron Microscopy Of L Stagnalis Digestive G...mentioning
confidence: 92%
See 1 more Smart Citation
“…A detailed description and characterization of MWCNTs can be found in Politowski et al ( 40 , 41 ) and Weise et al ( 27 ). Agglomerates with their typical cross-link structure and single strands of MWCNTs displaying a spiral shape with some irregularities were identified ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Further, particles without antibacterial properties, such as microplastics, are able to promote plasmid transfer due to providing novel surfaces for biofilm formation and hence donor-recipient interactions with intense cell-cell contact ( 25 ). Garacci et al ( 26 ) and Weise et al ( 27 ) demonstrated a type of network formation between graphene and MWCNTs with the extracellular polymeric substances of benthic organisms. Accordingly, it is also possible that bacteria colonize MWCNT agglomerates, which could facilitate biofilm formation or promote bacterial agglomeration ( 28 ), thus promoting horizontal gene transfer.…”
Section: Introductionmentioning
confidence: 99%